A world between the worlds. - Nair, Varsha (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Vietnam-based Finnish artist Maritta Nurmi recently exhibited her unique paintings in an exhibition titled "World between the World" at Numthong Gallery, Bangkok.